2005
DOI: 10.1111/j.1471-4159.2005.03506.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoisolation of two synaptic vesicle pools from synaptosomes: a proteomics analysis

Abstract: The nerve terminal proteome governs neurotransmitter release as well as the structural and functional dynamics of the presynaptic compartment. In order to further define specific presynaptic subproteomes we used subcellular fractionation and a monoclonal antibody against the synaptic vesicle protein SV2 for immunoaffinity purification of two major synaptosome-derived synaptic vesicle-containing fractions: one sedimenting at lower and one sedimenting at higher sucrose density. The less dense fraction contains f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
188
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(207 citation statements)
references
References 79 publications
15
188
2
Order By: Relevance
“…Consistent with previous results of Morciano et al (31), Western blot analysis showed that the synaptic vesicle markers synaptogyrin-3, synaptophysin, SV2, and VMAT 2 were distributed throughout the entire gradient (Fig. 5A).…”
Section: Cytosolic Domains Of Vmatsupporting
confidence: 80%
“…Consistent with previous results of Morciano et al (31), Western blot analysis showed that the synaptic vesicle markers synaptogyrin-3, synaptophysin, SV2, and VMAT 2 were distributed throughout the entire gradient (Fig. 5A).…”
Section: Cytosolic Domains Of Vmatsupporting
confidence: 80%
“…Synaptosomes are small lipid vesicles that form from synapses and astrocytic process following mechanical disruption of brain tissue using a blender or homogenizer (Whittaker et al, 1963). Synaptosomes may contain pre-and postsynaptic elements; this is a potentially confounding problem, as many of the proteins that facilitate receptor localization, anchoring, and signaling may be present in both compartments (Carlin et al, 1980;Morciano et al, 2005). One recent study has made strides to address this problem.…”
Section: Biochemical Enrichment Of Postsynaptic Densitiesmentioning
confidence: 99%
“…Although synaptic vesicles are well characterized trafficking organelles (3)(4)(5)(6)(7), to date, few attempts to purify and characterize axonally transported vesicular compartments at the morphological and biochemical level have been carried out. These include dense-core granulated vesicles transporting the presynaptic active zone components Piccolo and Bassoon to nascent synapses (8) and retrograde signaling endosomes (9 -11).…”
mentioning
confidence: 99%